Reconceptualising Domestic Violence as ‘Domestic Torture’ - Shazia Qureshi (Journal of Political Studies, 2013)
This paper attempts to capture the efforts of those feminist scholars, who call for the expansion of the human right law’s norm of torture prohibition, to encompass domestic violence against women incidents (McQuigg, 2011: 6). It also assesses the prospects to explore whether certain aggravated forms of domestic violence against women could make a qualifying case for torture. It seeks to propose that certain acts of domestic violence, particularly those having atrocious elements, would fall into the ambit of torture, as defined in human right law. The comparison between two types of violence will be helpful in deepening the understanding of the true nature of brutalities involved in the abuse that occurs within the home. Once recognised as torture, the ‘privacy’ and the ‘normalcy’ aspect of domestic violence against women will be challenged and be more open to scrutiny. It will no longer be deemed as an issue outside of state intrusion, it would rather be universalised and accordingly receive the attention it deserves.